A STUDY ON THE SOCIO-ECONOMIC CONDITIONS OF NORTH INDIAN MIGRANT WORKERS IN CHENNAI CITY (International Journal of Food and Nutritional Sciences, 2025)
Migration has become an integral component of India’s labour market, driven by regional disparities in employment opportunities and economic development. The present study examines the socio-economic conditions of North Indian migrant workers in Chennai city, with particular emphasis on their financial status, employment patterns, and working conditions. The study is based on both primary and secondary data. Primary data was collected through a structured questionnaire from 150 respondents, out of which 144 responses were received, and 6 were excluded due to incomplete information, resulting in a final sample of 138 respondents for analysis. The study adopts a descriptive research design and employs simple statistical tools such as percentage analysis and averages. The findings reveal that the majority of migrant workers belong to the economically active age group and are predominantly employed in the manufacturing, service, and construction sectors. Although migration has improved their employment opportunities, their income levels remain moderate, with a significant proportion earning within the lower and middle-income categories. The analysis further indicates that a large number of migrant workers lack access to social security benefits such as health insurance, provident fund, and paid leave. Hypothesis testing using the Chi-square method shows a significant association between employment sector and access to social security, while income differences across sectors are not statistically significant. The study also identifies key challenges faced by migrant workers, including low wages, long working hours, poor housing conditions, and limited access to healthcare. The study concludes that while migrant workers contribute significantly to Chennai’s economic growth, their socio-economic conditions remain vulnerable. It emphasizes the need for policy interventions focusing on skill development, improved working conditions, social security coverage, and better living standards to ensure inclusive and sustainable development.